2007
DOI: 10.1208/pt0804092
|View full text |Cite
|
Sign up to set email alerts
|

Physical mechanical and tablet formation properties of hydroxypropylcellulose: In pure form and in mixtures

Abstract: The aim of the study was to analyze hydroxypropylcellulose (HPC) in pure form and in excipient mixtures and to relate its physical and chemical properties to tablet binder functionality. The materials used were Klucel hydroxypropylcellulose grades ranging from low to high molecular weight (80-1000 kDa) of regular particle size (250 μm mean size) and fine particle size (80 μm mean size). These were compared with microcrystalline cellulose, spray-dried lactose, and dicalcium phosphate dihydrate. Thermal behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 21 publications
3
42
0
1
Order By: Relevance
“…It is a semi-crystalline polymer with relatively low T g and a high degree of amorphous content, which causes high molecular mobility and plasticity [1]. Similarly to other structural analogs of cellulose, HPC can be treated as a natural material, that is biocompatible with human tissues (including blood), nontoxic and relatively low cost [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is a semi-crystalline polymer with relatively low T g and a high degree of amorphous content, which causes high molecular mobility and plasticity [1]. Similarly to other structural analogs of cellulose, HPC can be treated as a natural material, that is biocompatible with human tissues (including blood), nontoxic and relatively low cost [2].…”
Section: Introductionmentioning
confidence: 99%
“…For the formulation variables, we have identified the binder level and source, disintegrant level, and Mg stearate type as the highest risk variables that should be examined when developing the design space. For this formulation, the binder was HPC; our previous results (4) and the literature have shown that physical-chemical properties of HPC (25) and the level in a roller compaction granulation formulation (26) can affect the mechanical properties of a tablet and the drug release rate. Based upon this information, we studied the source and level of HPC; because different sources of HPC are made from different feed stocks, different manufacturing methods and different processing conditions can affect the physical-chemical properties of HPC and hence product quality.…”
Section: Resultsmentioning
confidence: 99%
“…Their rigidity may have been enhanced by the intramolecular hydrogen bonding [11] that may have been strengthened in the presence of bound-water before drying. Furthermore, hardness of a tablet is dependent on its ability to undergo plastic deformation [19,20]. Lyophilization may have improved their plastic deformation thereby increasing the cohesive forces between the polymer particles which led to harder tablets.…”
Section: Discussionmentioning
confidence: 99%